Researches on data encryption scheme based on CP-ASBE of cloud storage. (24th July 2019) - Yang, Xiaohui; Ding, Wenqing
The ciphertext-policy attribute-set based encryption (CP-ASBE) based on a single authorisation centre easily becomes the security bottleneck of the system. With the support of trusted measurement technology, a novel method of CP-ASBE based on multiple attribute authority (AA) is proposed to solve this problem, and an encryption scheme is designed for cloud storage, which includes data storage, data access, data encryption and trusted measurement scheme for AA. The security performance and time cost of the encryption scheme are simulated, and the results show that the scheme can improve the security of users' data in the cloud storage environment.